CYTOTOXIC ACTIVITY OF SELECTED PLANTS USED IN ETHNOMEDICINE IN WESTERN NIGERIA - Sowemimo, A.; Van De Venter, M.; Baatjies, L.; Koekemoer, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Seventeen plants [Sapium ellipticum (Hocsht) Pax (Euphorbiaceae), Combretum paniculatum Vent (Combretaceae), Celosia trigyna Linn (Amaranthaceae), Pupalia lapacea (Linn) Juss (Lythraceae), Annona muricata Linn (Annonaceae), Justica extensa T. Anders (Acanthaceae), Hedranthera barteri (Hook f) Pichon (Apocynaceae), Alternanthera sessilis (Linn) D.C (Amaranthaceae), Ethulia conyzoides Linn f (Compositae), Lannea nigritiana (Sc Elliot) Keay (Anacardiaceae), Combretum zenkeri Engl & Diels (Combretaceae), Combretum molle R.Br (Combretaceae), Adenanthera parvonina Linn (Leguminosae), Lannea acida A.Rich (Anacardiaceae), Cyathula achyranthoides (H.B & K) Moq (Amaranthaceae), Drymaria cordata (Linn) Willd (Caryophyllaceae) and Cyathula prostata (Linn) Blume (Amaranthaceae) are used in herbal medicine for the treatment of cancer [1]. The methanolic extracts of these plants were evaluated for cytotoxicity at concentrations of 250 and 500 µg/ml using the Hela cell line (cervix tumor cell line) to validate the ethnobotanical uses of the plants and compare their activities. Sapium leaves, C. paniculatum leaves, Celosia leaves, Annona leaves, Drymaria leaves and C. prostata leaves showed 60-80% inhibition, Hedranthera leaves 50% inhibition, Pupalia leaves, Justica leaves, Alternanthera leaves, Ethulia leaves, Sapium stembark, Lannea stembark, C. zenkeri root showed less than 50% inhibition while C. molle leaves, Alternanthera fruits and L. acida stembark showed no inhibition at all. However, Sapium and Annona leaves showed activity comparable to the reference compound Cisplatin and both plants had greater cytotoxic activity than C. paniculatum, Celosia, Drymaria and C. prostata. Acknowledgement: The authors would like to thank Profs Coker and Ketiku for providing the Annona leaves.